Join IDNLearn.com and start getting the answers you've been searching for. Find reliable solutions to your questions quickly and easily with help from our experienced experts.
Sagot :
Let's tackle the given problem step-by-step.
We need to evaluate two composite functions based on the given functions [tex]\( f(x) = x^2 - 7x \)[/tex] and [tex]\( g(x) = x + 9 \)[/tex].
(a) [tex]\((f \circ g)(-1)\)[/tex]
To find [tex]\((f \circ g)(-1)\)[/tex], we need to evaluate the inner function first and then the outer function:
1. Calculate [tex]\( g(-1) \)[/tex]:
[tex]\[ g(-1) = -1 + 9 = 8 \][/tex]
2. Now, we substitute this result into [tex]\( f(x) \)[/tex]:
[tex]\[ f(g(-1)) = f(8) \][/tex]
3. Calculate [tex]\( f(8) \)[/tex]:
[tex]\[ f(8) = 8^2 - 7 \cdot 8 = 64 - 56 = 8 \][/tex]
Therefore,
[tex]\[ (f \circ g)(-1) = 8 \][/tex]
(b) [tex]\((g \circ f)(-1)\)[/tex]
To find [tex]\((g \circ f)(-1)\)[/tex], we again need to evaluate the inner function first and then the outer function:
1. Calculate [tex]\( f(-1) \)[/tex]:
[tex]\[ f(-1) = (-1)^2 - 7 \cdot (-1) = 1 + 7 = 8 \][/tex]
2. Now, we substitute this result into [tex]\( g(x) \)[/tex]:
[tex]\[ g(f(-1)) = g(8) \][/tex]
3. Calculate [tex]\( g(8) \)[/tex]:
[tex]\[ g(8) = 8 + 9 = 17 \][/tex]
Therefore,
[tex]\[ (g \circ f)(-1) = 17 \][/tex]
So, the final results are:
[tex]\[ (a) (f \circ g)(-1) = 8 \][/tex]
[tex]\[ (b) (g \circ f)(-1) = 17 \][/tex]
We need to evaluate two composite functions based on the given functions [tex]\( f(x) = x^2 - 7x \)[/tex] and [tex]\( g(x) = x + 9 \)[/tex].
(a) [tex]\((f \circ g)(-1)\)[/tex]
To find [tex]\((f \circ g)(-1)\)[/tex], we need to evaluate the inner function first and then the outer function:
1. Calculate [tex]\( g(-1) \)[/tex]:
[tex]\[ g(-1) = -1 + 9 = 8 \][/tex]
2. Now, we substitute this result into [tex]\( f(x) \)[/tex]:
[tex]\[ f(g(-1)) = f(8) \][/tex]
3. Calculate [tex]\( f(8) \)[/tex]:
[tex]\[ f(8) = 8^2 - 7 \cdot 8 = 64 - 56 = 8 \][/tex]
Therefore,
[tex]\[ (f \circ g)(-1) = 8 \][/tex]
(b) [tex]\((g \circ f)(-1)\)[/tex]
To find [tex]\((g \circ f)(-1)\)[/tex], we again need to evaluate the inner function first and then the outer function:
1. Calculate [tex]\( f(-1) \)[/tex]:
[tex]\[ f(-1) = (-1)^2 - 7 \cdot (-1) = 1 + 7 = 8 \][/tex]
2. Now, we substitute this result into [tex]\( g(x) \)[/tex]:
[tex]\[ g(f(-1)) = g(8) \][/tex]
3. Calculate [tex]\( g(8) \)[/tex]:
[tex]\[ g(8) = 8 + 9 = 17 \][/tex]
Therefore,
[tex]\[ (g \circ f)(-1) = 17 \][/tex]
So, the final results are:
[tex]\[ (a) (f \circ g)(-1) = 8 \][/tex]
[tex]\[ (b) (g \circ f)(-1) = 17 \][/tex]
We value your participation in this forum. Keep exploring, asking questions, and sharing your insights with the community. Together, we can find the best solutions. Your questions find answers at IDNLearn.com. Thanks for visiting, and come back for more accurate and reliable solutions.